Peningkatan Pembelajaran Tematik Terpadu Menggunakan Model Kooperatif Tipe Think Pair Share (TPS) di Sekolah Dasar - Mutiaramses, Mutiaramses; Zuryanty, Zuryanty (Universitas Negeri Padang, 2021)
The results of integrated thematic learning in primary schools are currently unsatisfactory and have not been implemented in accordance with the demands of integrated thematic learning, it can be seen from the large number of students who obtain the value of learning outcomes under Minimal Mastery Learning. To improve student learning outcomes can be done in various ways, one of them applying the cooperative learning model Think Pair Share (TPS) type in learning. This study aims to improve student learning outcomes using the TPS model in integrated thematic learning. This research is a classroom action research with research subjects of all fifth grade students of SD Negeri 03 Pandam Gadang consisting of 12 men and 8 women. The instruments used for data collection are tests and non-tests. To find out the success of the learning implementation plan, the learning implementation and learning outcomes are measured by the RPP observation sheet, the observation sheet of the learning aspects of the teacher and students, as well as the results of the test in the form of evaluation questions done by students. The results showed an increase. This can be seen from the average observations of RPP Cycle I which were 86.11% (B) and 91.66% (SB), increasing in cycle II to 94.44% (SB). This is also seen in the average results of the implementation of learning aspects of the first cycle of teachers is 79.16% (C) and 87.5% (B) increased in the second cycle to 91.66% (SB). In the aspect of students, the average cycle I was 75.00% (C) and 87.5% (B) increased in cycle II to 91.66% (SB). On the average student learning outcomes cycle 1 namely 74.56 (C) and 83.37 (B) increased in cycle 2 to 85.14 (B) Based on these results it can be concluded that using the model Think Pair Share can improve learning outcomes students on integrated thematic learning in class V.